Dual-band bandpass filter for software defined radio and 5G. Issue 7 (11th September 2020) - Chang, Wei-Chung; Tu, Wen-Hua
Abstract: This paper presents the filter design in the student design competition of EuMW 2019. This contest motivates students for the design and implementation of a dual-band bandpass filter able to get outstanding performance, where different implementation technologies, such as microstrip, coplanar, multilayer microstrip, substrate integrated waveguide, and some others can be effectively employed. Filters are evaluated by considering a figure of merit (FoM) defined by the insertion loss level, selectivity, spurious-free response, and size. To this end, three viable dual-band bandpass filters with different feeding technologies, resonators, and design topologies are investigated for the optimal FoM.